Influence of exogenous, physiological and factors of chronic inflammatory process on indicators of disturbances of adaptive processes of the person - Sokolovskaya, Irina; Kryachok, Irina; Chorna, Inna; Semeniv, Igor; Kotuza, Andriy; Hryhorieva, Nataliia; Plakhotnik, Olga; Zarytska, Valentyna; Zhuravel, Vladimir; Kmetyuk, Yaroslav; Kondratiuk, Alla (Київський національний університет імені Тараса Шевченка, 2020)
Changes in laboratory parameters can be caused by physical, chemical, biological and other external factors, depending on physiological conditions, in most cases they have an adaptive nature, and it is not always possible to distinguish them from physiological fluctuations. At the same time, obvious shifts in laboratory parameters may indicate a violation of adaptation processes and damage of tissues and organs, despite the absence of clinical manifestations of a disease.
Keywords: platelet aggregation; Willebrand factor; thrombosis; fibrin; hemostasis system; inflammation; exogenous; chemical and physiological factors